Identification of a novel subtype of SPP1 + macrophages expressing SIRPα: implications for tumor immune evasion and treatment response prediction - Chen, Kun; Li, Yida; Ni, Jianjiao; Yang, Xi; Zhou, Yue; Pang, Yechun; Ye, Ruiting; Chen, Hongru; Yu, Silai; Wang, Peng; Zhu, Zhengfei (Experimental hematology & oncology, 2024)
SPP1 + macrophages are among the major phagocytic cells, yet promoting tumor immune evasion and predicting unfavorable prognosis, in various cancer types. Meanwhile, the predictive value of the abundance of SPP1 + macrophages in patients receiving immunotherapy remains debatable, indicating the potential existence of subtypes of SPP1 + macrophages with diverse biological functions. The single cell RNA sequencing data of myeloid cells integrated from several cancers including esophageal squamous cell carcinoma was analyzed for characterizing the function and cellular interactions of SPP1 + macrophages expressing SIRPα. Multiplexed immunohistochemistry was used to quantify the quantity and spatial distribution of SPP1 + macrophages expressing SIRPα. Kaplan-Meier method was used for survival analysis. In vitro and in vivo studies investigating the function of SPP1 + macrophages were performed. SPP1 + macrophages possessed a high phagocytic signature and could engulf more tumor cells in vitro and in vivo. SIRPα expression could represent the phagocytic activity of SPP1 + macrophages and delineated subsets of SPP1 + macrophages with different functions. SPP1 + SIRPα + macrophages showed close spatial distance to tumor cells and positively correlated with PD1 + CD8 + T cells. A high abundance of SPP1 + SIRPα + macrophages at baseline corresponded to patients' response to PD-1/PD-L1 inhibitors. A novel subtype of SPP1 + macrophages expressing SIRPα was identified and their abundance predicted patients' response to PD-1/PD-L1 inhibitors.